HPLC Methods for Pharmaceutical Analysis - Lunn, George (John Wiley & Sons, 2011)
Analytical chemists and researchers will find a battery of useful features that make this practical new resource a welcome addition to their reference library: Detailed procedures for each drug are listed together making it easy to combine features of different methods into a customized approach.